2020
DOI: 10.1021/acscatal.0c02770
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Tuned N-Heterocyclic Carbene Ligands for the Efficient Formation of Hindered Products in Ru-Catalyzed Olefin Metathesis

Abstract: Formation of tetrasubstituted C–C double bonds via olefin metathesis is considered very challenging for classical Ru-based complexes. In the hope to improve this condition, three ruthenium olefin metathesis catalysts bearing sterically reduced N -heterocyclic carbene (NHC) ligands with xylyl “arms” were synthesized, characterized using both computational and experimental techniques, and tested in a number of challenging reactions. The catalysts are predicted to initiate much faster than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…We postulated that Grela catalyst A with the smaller o-xylyl groups of the imidazolinyl ligand was more suitable for the facile coordination of the substrate than D with the mesityl groups. 36 Indeed, we found that A cyclized the A-ring at a lower temperature (60 °C) with lower catalyst loading (10 mol %), delivering 6 in 81% yield with 18% of recovered 33 (entry 6). In this metathesis reaction, the addition of A in four portions and argon bubbling to remove the residual ethylene were essential for maintaining the catalytic efficiency of A.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We postulated that Grela catalyst A with the smaller o-xylyl groups of the imidazolinyl ligand was more suitable for the facile coordination of the substrate than D with the mesityl groups. 36 Indeed, we found that A cyclized the A-ring at a lower temperature (60 °C) with lower catalyst loading (10 mol %), delivering 6 in 81% yield with 18% of recovered 33 (entry 6). In this metathesis reaction, the addition of A in four portions and argon bubbling to remove the residual ethylene were essential for maintaining the catalytic efficiency of A.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…The reactivity of D was enhanced upon replacing toluene with C 6 F 5 CF 3 : 50 mol % of D enabled the generation of 6 in 58% at 120 °C (entry 4) and in 83% at 80 °C (entry 5). We postulated that Grela catalyst A with the smaller o -xylyl groups of the imidazolinyl ligand was more suitable for the facile coordination of the substrate than D with the mesityl groups . Indeed, we found that A cyclized the A-ring at a lower temperature (60 °C) with lower catalyst loading (10 mol %), delivering 6 in 81% yield with 18% of recovered 33 (entry 6).…”
Section: Resultsmentioning
confidence: 90%
“…Noteworthy, data reported in the literature [5] allows to compare Ru6 also with the state-of-the-art complex bearing a medium-size NHC, Ru7. [5,19] Interestingly, while this trend is preserved for the derivative of isopulgeol (2 f), the RCM reaction of a 1 g-bearing one terminal and one geminally disubstituted CÀ C double bond, based on a sesquiterpene alcohol, bisabolol-leads to almost quantitative conversion for both isomers of Ru6. Importantly, also in this case the productivity of cis-Ru6 was ahead of those exhibited in the same reaction by the SITol-bearing Ru2, an industry-standard tool designed particularly for such challenging transformations (Scheme 3, row B).…”
Section: Methodsmentioning
confidence: 99%
“…In these challenging reactions cis-Ru6 outdistanced also its closest structural analogue-the phosphine-containing catalyst Ru2 [3a] -offering 9 to 56 pp (percent points) higher conversions. Noteworthy, data reported in the literature [5] allows to compare Ru6 also with the state-of-the-art complex bearing a medium-size NHC, Ru7. [5,19] Interestingly, while this trend is preserved for the derivative of isopulgeol (2 f), the RCM reaction of a 1 g-bearing one terminal and one geminally disubstituted CÀ C double bond, based on a sesquiterpene alcohol, bisabolol-leads to almost quantitative conversion for both isomers of Ru6.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we decided to investigate the performance of various Ru-catalysts in RCM, leading to the formation of a tetrasubstituted olefin 47. Unfortunately, quick reconnaissance shown that a specialized ruthenium catalyst with a small NHC ligand (Planer et al, 2020) decomposes very quickly under reaction conditions in water. Similarly, Ru9BARF with a sterically augmented SIPr-like ligand gave no conversions in the case of the formation of a tetrasubstituted C-C double bond.…”
Section: Scope and Limitation Study Of Metathesis Reactions Using Mic...mentioning
confidence: 99%